Planning for production in construction: controlling costs in major capital projects - Caffieri, J.; Love, Peter; Whyte, A.; Ahiaga-Dagbui, D. (Taylor & Francis, 2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. There has been limited research that has examined how the public sector can guarantee their major capital projects are delivered within budget. A Strategic Asset Management Framework (SAMF) developed by the Western Australian State Government, was implemented that ensured their major capital projects were delivered within 5% of their budget. Interviews were conducted with stakeholders who had participated in the delivery of capital projects using the SAMF to understand how it had been used to successfully deliver projects. The interviews highlighted the importance of the SAMF in addressing optimism bias and strategic misrepresentation with the use of independent auditors. The research provides invaluable insights from practice that have been used to control and manage the capital expenditure of assets. Such knowledge is pivotal for ensuring strides are made forward to addressing the cost growth phenomenon that continues to plague major capital projects.